Effect of Preheating on the Parameters of Laser Keyhole Welding Process: Analytical Study - Hamadi, Oday A.; Khashan, Khawla S. (Iraqi Journal of Laser, 2006)
In this work, results of a mathematical analysis of the role of workpiece preheating in laser keyhole welding were presented. This analysis considered the steady-state welding as well as certain range of boundary conditions over which preheating effect would be indicated. This work is an attempt to interpret the role of preheating to increase welding depth and perform keyhole welding with high quality using physical and thermal properties of steel alloys.